Management of Localized Gingival Overgrowth in Patient under Fixed Orthodontic Treatment: A Case Report - Neira N. Sakinah; Yuliana M. D. Arina; Depi Praharani; Peni Pujiastuti; Desi S. Sari; Melok A. Wahyukundari (Universitas Sam Ratulangi, 2022)
Abstract: Recently, the need for orthodontic treatment has increased along with the increasing need and public awareness of the importance of dental and oral health. During treatment, problems sometimes occur with periodontal tissue. Orthodontic devices that bond to the tooth surface can cause difficulties in controlling plaque, especially in marginal areas which can cause inflammation and gingival overgrowth. Too high tensile strength and weak tissue capacity are also the factors that can cause gingival overgrowth. This case report described the management of gingival growth in a patient under fixed orthodontic treatment. We reported an 18-year-old female patient with a good systemic condition that had gingival overgrowth localized on the anterior part of mandibula. The surgical intervention was performed by using conventional surgical methods. Its goal was to remove the gingival pocket, therefore, the plaque could be easily controlled. The use of a scalpel was considered very effective for eliminating excessive gingiva. Two weeks after surgical treatment, the gum resulted in good repair. The continuity of orthodontic treatment could be achieved properly after 3-month surgical treatment. Instructions and motivation to maintain oral hygiene were important to avoid recurrence. In addition, multidisciplinary dentistry between orthodontist and periodontist was needed to achieve a better result. Keywords: gingival overgrowth; gingivectomy; orthodontic appliance